(untitled) (Annual of the Faculty of Philosophy in Skopje, 2019)
Initiatives for social reforms are part of the governmental agendas of almost all European countries. The introduction of support for the households by guaranteeing minimum incomes, activation of the social assistance beneficiaries, as well as delivery of integrated services in the local community are the main challenges of the contemporary social protection systems. Reflecting the significance of institutions (establishment, organization and administrative capacity) as a key condition for achievement of socially-accepted goals, European countries, in the last few decades, have been implementing administrative reforms of social protection systems. The countries are searching for improved institutional arrangements for maximization of policy effects directed towards social inclusion and reduction of social tensions in the societies. In most cases, countries introduce administrative modalities based on managerial doctrines of governing (new public management), while others experiment with a certain form of decentralization which usually includes initiatives for local provision of social services and, in certain cases, integration with employment services. Yet, although a part of the administrative reforms are being implemented with the same purpose, they lead to different institutional solutions as a result of the social context in which they are framed. This article gives an overview of the trends in the development of the social protection systems of the European countries, which despite the efforts for convergence of social policies and the creation of a unified social model, continue to show diversity of legal and institutional solutions at the national level.